PENJELAJAHAN MARWAH GORGA DALAM KARYA FILM DOKUMENTER BUDAYA DARI BUMI BATAK - Reynaldo Apriasie Sinaga; Enok Wartika; Retno Dwimarwati (Institut Seni Budaya Indonesia Bandung, 2020)
Documentary film is a visualization of facts and reality. The film is packaged based on a team's research either done in depth or just a surface study. However, the contribution of field data is one of the strengthens that proves the quality of a documentary film. Documentary film